THE ROLE OF OPSONINS IN THE CLEARANCE OF LIVING AND INERT PARTICLES BY CELLS OF THE RETICULOENDOTHELIAL SYSTEM - Jenkin, Charles R. (The Rockefeller University Press, 1961)
An investigation of the clearance of bacteria and colloids from the blood stream of mice has shown that both living and inert particles require serum factors (opsonins) in order that they may be phagocytosed by the macrophages of the reticuloendothelial system. It has been demonstrated that after the injection of a large dose of colloid there is a depletion of these serum opsonins which appears to account for the reduced rate of clearance of a second dose of colloid or living bacteria, since replacement of these factors leads to normal clearance. The significance of these results is discussed and it is suggested that in "blockaded" animals there is a depletion of serum opsonins rather than a saturation of phagocytic cells.